Eating Disorder Symptomatology and Identity Formation in Adolescence: A Cross-Lagged Longitudinal Approach - Verschueren, Margaux; Claes, Laurence; Bogaerts, Annabel; Palmeroni, Nina; Gandhi, Amarendra; Moons, Philip; Luyckx, Koen (Frontiers in Psychology, 2018)
Introduction. Eating disorder symptomatology, comprising both psychological and behavioral aspects of subclinical eating concerns, constitutes a clear precursor of developing eating disorders. It is crucial to investigate its antecedents and correlates to subsequently inform eating disorder prevention programs. The present study focused on identity formation, a core developmental task in adolescence, that has increasingly been linked to eating disorder development. Our main aim was to examine the temporal sequence between eating disorder symptomatology and identity formation. Methods. Data on eating disorder symptomatology and identity formation were collected in 530 high school students (at Time 1: mean age = 15 years; SD = 1.84; range: 12 to 18 years; 50.6% females) using self-report questionnaires at three annual measurement points. Cross-lagged structural equation modeling was performed to examine the directionality of effects. Results. Results indicated bidirectional effects between eating disorder symptomatology and identity formation. Identity confusion seemed to increase vulnerability to body dissatisfaction and bulimia symptoms, whereas identity synthesis seemed to protect against their development. Additionally, identity synthesis seemed to protect against the development of drive for thinness as well. At the same time, body dissatisfaction and bulimia symptoms positively predicted identity confusion and negatively predicted identity synthesis over time. Conclusions. The present study adds to the growing body of literature on identity and eating disorders by focusing on their temporal interplay in a community sample of adolescents. As bidirectional effects emerged, a greater emphasis on identity formation in eating disorder prevention programs is advocated.